Behavioural contexts for the expression of modern racism: The simulated juror paradigm - Riggs, Murray (1998)
The central tenet of modem racism theory is that, although overt prejudice seems to have declined, subtle forms of prejudice are still pervasive. The theory predicts that members of a majority racial group will discriminate against members of a minority racial group only when they feel that they can do so without appearing to be prejudiced. Thus, the occurrence of discrimination depends upon the nature of the behavioural context. The purpose of the present study was to explore the implications of modern racism theory in the behavioural domain by employing the simulated juror paradigm. The participants, 338 randomly selected residents of the city of Perth, read one of six versions of a hypothetical criminal case (burglary) varying the race of the defendant (Aboriginal or Caucasian) and type of jury instructions (none, evidence instructions, or non-prejudice instructions) and then made individual judgments about the defendant's guilt. The 2 X 3 design was analysed using log-linear (guilty/not guilty as a dichotomous dependant variable) and ANOVA (continuous measures of confidence in guilt judgment and personal opinion of guilt as dependant variables) analytical procedures. Analysis was also carried out on qualitative data ( why did you judge the defendant to be guilty I not guilty? ). The results indicated that race of the defendant and type of instructions had no effect on the judgments made by participants. The discussion raises the issue of variability in the salience of race and the social desirability for egalitarianism across social contexts, and explores possible limitations of modem racism theory as it is presently defined